Condiciones turísticas del caserío Huacamochal, distrito Usquil, provincia Otuzco - Región La Libertad, para formar parte del potencial circuito turístico Alto Chicama como alternativa para el desarrollo turístico local. - Uchida Silva, Keiko Nair (2018)
The present investigation called Caserío Huacamochal Tourist Conditions, Usquil district, Otuzco province - La Libertad region, to be part of the potential tourist circuit Alto Chicama as an alternative for local tourism development, aims to identify the tourist conditions of the Huacamochal Hamlet which —as it was necessary for a future enhancement of the tourist destination— was contrasted regarding of variables of the tourist system such as tourism resources, from which a tourism inventory of categorization and hierarchy of the resources of the village was obtained; the host community with a sample of 123 inhabitants, has the predisposition to participate in activities related to tourism and promote tourism in the area; the basic infrastructure, which shows routes and access roads in optimal conditions as well as an urban equipment that improves every year; and the tourist superstructure and political will, where the organization and planning of the Tourism Area of the District Municipality of Usquil is explained and the approach of its policies oriented to the tourism sector, through the Tourism Development Plan, taking into account the Institutional Operational Plan and the Annual Operating Plans. The conditions show that Huacamochal can be part of the potential Alto Chicama Tourist Circuit that includes the upper area of the Chicama River basin where the districts of Charat, Usquil and Huaranchal are located, which have tourism resources inventoried and recommended by MINCETUR; conforming altogether an alternative for the local tourist development that is being generated in the province of Otuzco.